The 12th ISDEV International Development Management Conference (IDMAC2017) (Halal-Green Development Management): Book of Abstract - ISDEV, Pusat Kajian Pengurusan Pembangunan Islam (Centre for Islamic Development Management Studies (ISDEV), 2017)
List of Abstracts Accepted (As Of 6th September 2017)